Transforming an Urban School System Progress of New Haven School Change and New Haven Promise Education Reforms (2010-2013) - Gonzalez, Gabriella C. (RAND Corporation, 2014)
In the 2010-2011 school year, two educational programs launched in New Haven, Connecticut: New Haven School Change, a sweeping K-12 educational reform to improve the learning of educational outcomes of its students, and New Haven Promise, a scholarship program intended to improve college-going culture and encourage graduates to attend college. This report documents a study of early progress in these programs.